The Effect of Aerobic Training and Vitamin D Supplementation on Blood Pressure in Elderly Women with Nonalcoholic Fatty Liver and Vitamin D Deficiency - Zahra Hoseini; Nasser Behpour; Rastegar Hoseini (Fasa University of Medical Sciences, 2019)
Background & Objective: The aim of this study was to investigate the effects of aerobic training (AT) and vitamin D (Vit D) supplementation on cardiovascular variables in elderly women with nonalcoholic fatty liver disease (NAFLD) and vitamin D deficiency. Materials & Methods: A total of forty women (60-65 years) with NAFLD (second or third grade) and vitamin D deficiency were recruited for the study. Participants were randomly assigned to four AT+Vit D, AT, Vit D, and control (C) groups and were allocated to receive either vitamin D (∼50000 IU • week for eight weeks) or placebo. The aerobic training protocol consisted of 40-60 minutes of aerobic training at 60% - 75% of HRmax, 3 times a week for eight weeks. Anthropometric indices along with systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) were measured and mean of arterial pressure (MAP) was calculated. Results: AT+Vit D, Vit D and AT groups demonstrated a significant decrease in SBP, DBP, and HR, (P < 0.05) while, C group showed a significant increase in the mentioned variables (P < 0.05). Also after 8 weeks, AT + Vit D and AT groups showed significant decrease in the mean of MAP (P = 0.001; P = 0.018). Compared to the control group, significant differences in the SBP, DBP, and HR were observed in all groups. The mean SBP was significantly lower in AT+Vit D group comparing with AT, Vit D, and C groups. Also, no significant differences were observed between AT and Vit D groups in all variables. Conclusion: AT developed significant improvement in cardiovascular variables indicating SBP, DBP, MAP, and HR in elderly women with NAFLD and vitamin D deficiency. Meanwhile, AT combined with Vit D decreased SBP more significantly that might be incorporated in the management programs of the patients suffering from NAFLD in order to augment improvement in their blood pressure.